Effects of the EU-enlargement on income convergence in the eastern border regions - Fredrik Wilhelmsson (Center for Social and Economic Research (CASE), 2009)
This paper analyses the effect of the EU enlargement process on income convergence among regions in the EU and in the Eastern neighbourhood of the EU. The data used is NUTS II regions in the EU and Oblasts' of Russia over the period 1996-2004. The estimation techniques used take into account both regional and spatial heterogeneity. The main findings are that the regional income differences are reduced within EU15. The income convergence within the EU is mainly driven by reductions in the differences across countries rather than by a reduction in regional differences within countries. When differences in initial conditions in the regions are controlled for by fixed regional effects there are strong evidences of convergence among regions in all studied country groups.
Keywords: R11; O18; 330; Income convergence; European integration; Border effects; EU-Mitgliedschaft; Räumliche Verteilung; Grenzregion; Wirtschaftliche Konvergenz; Europäische Integration; EU-Staaten; GUS-Staaten